Transforming Organic Farming as a Pillar of Healthy and Sustainable Food Consumption: A Systemic Innovation Perspective in the Post-Pandemic Era - Annisa Annisa (Livestock Science & Innovation Journal, 2025)
Changes in consumption patterns following the COVID-19 pandemic have shown a significant increase in demand for healthy and sustainable foods, including organic animal products. Organic farming is considered capable of addressing health, environmental, and ethical production challenges amidst the global food system crisis. However, most previous studies have focused on crop-based organic agriculture, with limited analysis on integrating livestock practices within systemic innovation frameworks in the post-pandemic context. This study aims to examine the strategic role of organic livestock farming in strengthening healthy food consumption, identify challenges and opportunities for systemic innovation, and formulate policy frameworks that encourage the integration of production with modern consumer preferences. The approach used is descriptive qualitative with a case study method in three regions: West Java, Bali, and Yogyakarta. Data collection involved in-depth interviews, field observations, and analysis of policy documents and consumption trends. Data were analyzed thematically and verified through source triangulation. The study found that consumption of organic animal products increased by 23% over the past five years. Innovations such as fermented natural feed, biofermenters, and digital distribution have been shown to enhance system efficiency and sustainability. Major challenges include access to inputs, regulations, and farmer literacy. Transforming organic livestock farming presents a systemic solution to achieving healthy and sustainable food security. Integrating technological innovation, local institutions, and consumer preferences is key to developing a resilient organic livestock system in the post-pandemic era.